2012
DOI: 10.1111/j.1478-3231.2011.02732.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutant HrasG12V and KrasG12D have overlapping, but non‐identical effects on hepatocyte growth and transformation frequency in transgenic mice

Abstract: Background Mouse hepatocarcinogenesis is associated with mutations in Hras but infrequently in Kras. The effect on carcinogenesis of developmental age at the time of ras mutation is unknown. Aim We sought to compare quantitatively the effects of expressing mutant H- or Kras genes in fetal versus adult mouse liver. Methods We established an inducible system of gene expression in mouse liver to define disease pathogenesis associated with activation of oncogene expression. Results Diffuse expression of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To our knowledge, this has only been described in mice. 19 In the case of branchio-ocular facial syndrome, absent radii has not been previously described in humans but knockout mice for TFAP2A show radial agenesis. 20 These cases demonstrate how prenatal ES expands our understanding of fetal presentations of various disorders (Table 4: ultrasound phenotypes and genotypes).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this has only been described in mice. 19 In the case of branchio-ocular facial syndrome, absent radii has not been previously described in humans but knockout mice for TFAP2A show radial agenesis. 20 These cases demonstrate how prenatal ES expands our understanding of fetal presentations of various disorders (Table 4: ultrasound phenotypes and genotypes).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, FINO2 exerts its effect by both indirectly inhibiting GPX4 enzymatic function and directly oxidizing iron, ultimately leading to widespread lipid peroxidation. HRAS, a mutated oncogenic RAS gene, was targeted by ML162, causing selective lethality in HRAS-expressing BJeLR cells ( Figueiredo et al, 2012 ). It has now been discovered that ML162 may not act as a direct biochemical inhibitor of GPX4, adding a layer of complexity to our understanding ( Cheff et al, 2023 ).…”
Section: Regulators Affecting Ferroptosis and Ferritinophagy Processesmentioning
confidence: 99%
“…showed that a constitutively active form of KRAS is more tumorigenic than that of NRAS in mouse models of colon cancer, possibly explaining why mutations in KRAS are more frequently observed than NRAS in human colon tumors [ 15 ]. However, the apparent biases in mutation frequencies among the RAS genes in human cancers could be caused by factors other than differential oncogenic characteristics of RAS isoforms, such as differences in expression levels or mutation rates due to different genomic locations among the RAS genes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%